Produksi Bioetanol Dari Pati Sorgum Dengan Variasi Penambahan Cordyceps Sinensis Dan Waktu Fermentasi - Novriandi, Rizky; Yenie, Elvi; Muria, Sri Rezeki (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Excessive human consumption and dependence on fossil fuels cause fuel reserves become depleted, while for the renewal takes thousands and even millions of years. To overcome fossil fuel dependency is carried sorghum starch conversion into bioethanol as a renewable energy. In this research, sorghum starch fermentation process using bacteria Saccharomyces Cerevisiae reviewed variations additions Cordyceps sinensis 0.5 g, 1 g, 1.5 g, and 2 g, to obtain bioethanol from sorghum starch with higher level. The purpose of this study to determine the effect of addition Cordyceps Sinensis variation conversion to bioethanol produced and determine the effect of variations in the fermentation time to conversion of bioethanol produced. Fermentation was conducted in 2 Liter fermentor with variations of fermentation time from 12, 24, 48, 72, until 96 hours, addition of Cordyceps Sinensis 0.5 g, 1 g, 1.5 g, and 2 g. Cordyceps sinensis role in improving the resilience microbial cells in the fermentation medium to produce bioethanol at higher level. The addition Cordyceps Sinensis can promote the growth microorganisms and fermentation activity. Sorghum starch fermentation process produce optimum conditions on addition Cordyceps Sinensis much as 1 gram and fermentation time of 96 hours with a bioethanol content of 2.124882% (v / v).Keywords: Bioethanol, Starch Sorghum, Saccharomyces Cerevisiae, Cordyceps Sinensis